Carbon sustainability and productivity of maize based cropping system under conservation agriculture practices in Indo-Gangetic plains - Jat SL; Parihar CM; Singh, A.K.; Jat, Mangi Lal; Jat, Kumar Raj (2011)
Tillage practices contribute greatly to the labour cost in modern intensive agriculture in any crop production system resulting in lower economic returns, especially in developing countries where there is most concern for sustainable production without degradation of the natural resource base (Jat et al., 2008). The traditional practice of growing these crops has limitations such as inconvenient input management when sown by broadcasting: improper plant geometry; uneven plant population resulting in inefficient utilization of space; and plant competition leading to low productivity and input efficiency. Shortage of water, labour and energy resources, together with inappropriate crop management practices and the adverse effects of conventional tillage on the carbon based sustainability index, as well as declining profit margins, are forcing farmers of Indo-Gangetic Plains (IGP) to switch over to conservation agriculture practices. Conservation agriculture with diversified maize-based cropping systems by inclusion of legume crops in sequence helps to overcome the major challenges viz. declining factor productivity and deterioration of the resource base, and also plays a vital role in sustainable agricultural production. Adoption of no-till practice helps in timely seeding of either of the crops, and hence leads to increase in productivity of different maize-based cropping systems. In the present study four cropping system were evaluated under three different tillage and crop establishment practices to assess the system productivity, carbon inputs and outputs and carbon based sustainability index. The study aims to develop conservation agriculture practices to increase the sustainability of the maize-based cropping systems in the IGP.